Police Perceptions of Police-Involved Overdose Outreach Program Effectiveness - Becker, Laurie T. (Journal of drug issues, 2021)
This study surveys police officers from three New England states to examine the perceptions officers hold toward the effectiveness of police-involved overdose outreach programs, the variables that serve as significant predictors for perceptions of program effectiveness, and the extent to which attribution theory can explain these perceptions. The majority of officers displayed positive perceptions of program effectiveness, and eight significant predictors were identified, including attribution theory which showed significance in explaining why police officers perceive these programs as effective. As an increasing number of police departments take a service-centered approach to working with individuals with substance use disorder, police-involved overdose outreach programs are becoming more commonplace. From the results of this study, practitioners are able to identify variables that predict officers’ views of program effectiveness. Equipped with this knowledge, increasing the support of these related concepts will help to subsequently increase the likelihood of officers viewing these programs as effective.